The road to London 2012: The lived stressor, emotion, and coping experiences of gymnasts preparing for and competing at the world championships - Nicholls, A. R.; Levy, A. R. (International Journal of Sport and Exercise Psychology, 2016)
The purpose of this study was to explore the lived stressors, emotions, and coping experiences of four international gymnasts. A variety of recurring stressors were reported by the gymnasts, such as performing poorly in training, expectations from other people, and coaches. Coping appeared to generate pleasant emotions in some instances, especially when it was effective. The gymnasts also experienced multiple emotions simultaneously, including unpleasant (e.g. anxiety) and pleasant emotions (e.g. excitement). The diaries also revealed the extent to which team members were affected by one another, such as when a team member suffered an injury that prevented him competing in an international event and the other team members experienced a variety of unpleasant emotions. The gymnasts also reported experiencing pleasant and unpleasant emotions simultaneously. As such, these findings add to the emerging literature that people can experience different emotions simultaneously and illustrate the importance of examining multiple emotions to capture the entire emotional experience.